2012
DOI: 10.3844/ajisp.2012.65.70
|View full text |Cite
|
Sign up to set email alerts
|

Role of Angiotensin-Converting Enzyme and Vitamin D Receptor Gene Polymorphisms in Cancer Anorexia-Cachexia Syndrome

Abstract: The ubiquitin-proteasome pathway is a crucial connection between aberrant immune system activation, systemic inflammation and Cancer Anorexia-Cachexia Syndrome (CACS), a syndrome that culminates in hyper-activation of the ubiquitin-proteasome pathway. Angiotensin directly up-regulates this pathway, while vitamin D down-regulates it indirectly through the insulin-like growth factor-1 pathway. We investigated the genetic predisposition towards CACS in a cancer population, examining Insertion/Deletion (I/D) polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It can therefore be hypothesized that the antineoplastic effects of GcMAF may also be influenced by such polymorphisms. Moreover, it should be kept in mind that the prognosis of patients affected by all types of cancers is dependent upon their nutritional and inflammatory status, which can be monitored by the Prognostic Inflammatory and Nutritional Index (PINI) 19 . The PINI score might therefore become part of the laboratory assessments performed in the course of GcMAF therapy, and - together with the assessment of serum nagalase activity testing and VDR polymorphisms - it may assist physicians in monitoring the response of individual patient to GcMAF and adjusting doses and schedules in the course of treatment, if required.…”
Section: Discussionmentioning
confidence: 99%
“…It can therefore be hypothesized that the antineoplastic effects of GcMAF may also be influenced by such polymorphisms. Moreover, it should be kept in mind that the prognosis of patients affected by all types of cancers is dependent upon their nutritional and inflammatory status, which can be monitored by the Prognostic Inflammatory and Nutritional Index (PINI) 19 . The PINI score might therefore become part of the laboratory assessments performed in the course of GcMAF therapy, and - together with the assessment of serum nagalase activity testing and VDR polymorphisms - it may assist physicians in monitoring the response of individual patient to GcMAF and adjusting doses and schedules in the course of treatment, if required.…”
Section: Discussionmentioning
confidence: 99%
“…This is an enzyme expressed on the surface of most cell types, including macrophages and T-lymphocytes and is associated with immune regulation, signal transduction and apoptosis (Havre et al, 2008;Hiromura et al, 2018). The PINI score was calculated as described by Fabris et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…If the literature on nagalase is relatively new and limited to a small, albeit significant, number of peerreviewed papers, the literature on CRP, an acute-phase protein that increases in the presence of infectious and inflammatory processes, is older and ampler and refers to a large number of conditions ranging from cancer (Allin and Nordestgaard, 2011) to autism (Brown et al, 2014), depression (McFarland et al, 2019, cardiovascular diseases (Cozlea et al, 2013), multiple sclerosis (Dowling and Cook, 1976) and anemia (Breiterman-White, 2006) to name a few. In a study on incurable cancer patients published in 2012, we demonstrated that CRP, integrated into the context of the Prognostic Inflammatory Nutritional Index (PINI) score, was a powerful marker for predicting overall survival (Fabris et al, 2012). Similar to nagalase, CRP may bear more pathogenic significance than simply being a marker; according to a recent paper "CRP is pathogenic in a number of diseases including hypertensive cardiovascular and kidney complications, diabetic nephropathy and acute and chronic kidney diseases" (Tang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it was recently demonstrated that the degree of the response of normal human monocytes to GcMAF is associated with individual VDR genotypes (Pacini et al, 2012a) and it can be hypothesized that also the response in terms of anti-neoplastic effects may be associated with such polymorphisms. Finally, it should be remembered that the prognosis for all types of cancers is dependent upon the nutritional and inflammatory status of the patient that can be monitored by the Prognostic Inflammatory and Nutritional Index (PINI) (Fabris et al, 2012). The PINI score therefore could become part of the laboratory assessment during GcMAF treatment and together with Nagalase testing and VDR gene polymorphism determination, it could help monitor the response of each individual patient allowing adjustment of the dose and the frequency of administration in order to obtain the optimum results.…”
Section: Resultsmentioning
confidence: 99%